Digital Content Assessment of Academic Library Websites: Evidence from NIRF (2024) Ranked Pharmacy Institutions in India - Madhu, S; Kannappanavar, B U (Information Research Communications, 2026)
Background Due to the rapid advancement of internet and communications technologies, academic users have changed their perception of finding relevant information within a few clicks. The importance of library websites/webpages has made library users one of the prime venues to find information within one unified window to multiple resources in an academic environment. Purpose To purpose the study to access the extent and quality of web elements present in academic library website/webpages of ‘NIRF’ ranked pharmacy institutes that were listed in 2024 of the National Institutional Ranking Framework (NIRF) that was adopted by the Ministry of Education, Government of India., based on predetermined criteria. Methodology The study was confined to the analysis of 85 library websites out of the top 100 institutions; the remaining fifteen institutions were excluded due to the absence of dedicated library webpages/websites or the availability of only minimal library information. Based on prior research, a standardized set of parameters was identified and structured into a checklist for the systematic evaluation of the selected websites. Results The study reveals marked inconsistencies in the structural design, visibility, and functional integration of pharmacy library websites. Although core resources such as print and electronic collections are widely represented, direct homepage access, independent web platforms, and the adoption of content management systems remain limited. Advanced research support tools, reference management systems, federated search facilities, and mobile applications show minimal implementation. Furthermore, inadequate Web 2.0 integration, insufficient essential service information, and limited content updates collectively indicate weak emphasis on user-centric design and digital innovation. Conclusion This study assists librarians and web developers in optimizing their websites so that users can quickly locate relevant resources, services, and information in general.
Keywords: Web Content Analysis; Content Evaluation; Library Websites; Webpage; Web 2.0; NIRF; India.